Development and characterization of vancomycin-loaded levan-based microparticular system for drug delivery - SEZER, ALİ DEMİR; TOKSOY ÖNER, EBRU; RAYAMAN, ERKAN (TAYLOR & FRANCIS LTD, 2017)
Encapsulation of vancomycin (VANCO) into biodegradable levan microparticles was achieved using a simple preparation technique. Microparticles were prepared by using levan polysaccharide produced by a halophilic bacterium Halomonas smyrnensis AAD6(T). To optimize efficiency of encapsulation process by precipitation method, three parameters were studied: drug and polymer concentrations and preparation rotating speed. The particles were characterized in vitro. The size of levan microparticles was changed between 0.404 mu m and 1.276 mu m. The surface charge was detected between +4.1 mV and +6.5 mV. The highest drug encapsulation capacity of the system was 74.7% and was depending on the polymer concentration. In dissolution studies, initial burst effect around 10-20% from all the formulations was observed and then the release was slowed down and continued at a constant level. In vitro antibiotic release from the microparticles was controlled with the drug carrier system and release fit to Higuchi kinetic model. All the released samples collected at different time intervals during dissolution studies have exhibited intrinsic bactericidal activity against Bacillus subtilis ATCC 6633. WST-1 cell proliferation and viability studies showed that VANCO-loaded levan microparticles at concentrations between 100 mu g/mL and 1000 mu g/mL were nontoxic to L929 cells. As conclusion, levan microparticulate system could be a potential carrier of antibiotic drugs such as VANCO.
Keywords: Controlled release; levan; microparticle; polysaccharide; vancomycin; COLON-SPECIFIC DELIVERY; IN-VITRO; NANOPARTICLES; MICROSPHERES; RELEASE; FILMS; BIOPOLYMER; PARAMETERS; PARTICLES; SUBSTRATE